Index of Online Teaching Stress and Quality of Life among Nurse Educators during COVID-19 - Shiv Kumar Mudgal; Kavita Verma; Suchpreet Kaur Gill; Rakhi Gaur; Digpal Singh Chundawat; Ravikant Sharma (Indian Journal of Psychiatric Nursing)
Background: With sudden changes in the worldwide education system due to COVID-19 impact and limited available resources, nurse educators have been suffering from online teaching stress in this year, which is thought to affect their quality of life (QOL). The aim of this study was to ascertain the index of online teaching stress and QOL among nurse educators during COVID-19. Subjects and Methods: In this cross-sectional study 162 nurse educators were recruited through a convenient sampling technique. Online survey was employed using socio-demographic questionnaire, online teaching stress scale, and World Health Organization QOL BRIF-26 to collect data. IBM Statistical Package for the Social Sciences (SPSS) Version 23 was used for statistical analysis. Results: Among all participants, 22% and 51% of participants reported severe and moderate level of online teaching stress respectively. The highest and lowest overall QOL was reported in the social relationship (70.29 ± 20.5) and physical health (54.54 ± 13.73) domain. Online teaching stress scores were significantly associated with gender (P = 0.012), teaching experience (P < 0.001), salary (P < 0.001), job satisfaction (P < 0.001), satisfaction with organization (P < 0.001). Online teaching stress scores were significantly negative correlated with all four domains of QOL. Marital status and monthly salary were the indicators of online teaching stress. Teaching experience, salary, and job satisfaction appeared to be robust predictors for domains of QOL (P < 0.05). Conclusion: The findings suggest that effective interventions primarily focusing on improving the availability of resources, training, and empowerment activities are necessary to decrease the negative effect of stress on QOL.